Living Lab Concept for Sensor Based Energy Performance Assessment of Houses - Farrukh Arif; Muhammad Wasay Uz Zaman; Rabia Khalid (NAROTAMA UNIVERSITY, Indonesia, 2022)
All the social, economic and industrial development depends on the availability of energy. Since energy demand is increasing exponentially throughout the world, more and more CO2 is being emitted out into the atmosphere, giving rise to global warming. Therefore, establishing a sustainable environment is becoming increasingly important. It has been found through research that domestic sector contributes a great deal to the rising energy consumption. Due to prevailing energy crisis, efforts are being made to reduce the increasing energy consumption and make efficient use of energy by making the buildings energy efficient. For this, realistic assessment of energy use patterns in existing houses and buildings is necessary to assure dataset accuracy. Living lab concept integrated with sensor technologies can be used for assessment of such patterns. This paper presents living lab concept for sensor-based energy performance assessment of Houses. First, detailed literature review to benchmark concepts of energy efficiency of buildings, living labs concept, sensor based assessment, energy audit, and application of living lab concept has been discussed. Thereafter, sensors based living lab assessment and living lab approach has been introduced as being utilized by the author in a research project for development of guidelines for energy efficient housing. The paper also highlights important parameters to be monitored that effect energy performance. The concept reflects usefulness of living lab concept for sensor-based energy performance assessment of houses that help in substantial reduction in the energy consumption. As such data can be utilized for both realistic energy simulations by improving level of development of models as well as better usage comparisons with modeled analysis, hence helping in identifying true and effective improvement measures